ANALISIS MANAJEMEN RISIKO DAN STRATEGI PEMASARAN AGROINDUSTRI KOPI BUBUK (Studi kasus Agroindustri Kopi Bubuk Cap Gunung Betung) - Asila Jelita Maharani; Dwi Haryono; Adia Nugraha (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
This study aims to analyze the production performance, risk management and marketing strategies agroindustry Gunung Betung coffee powder in Bandar Lampung City. This research use a case study method in Kopi Bubuk Cap Gunung Betung agroindustry. Data collection was conducted on Desember 2019-Januari 2020. This study uses qualitative and quantitative descriptive method. Production performance was analyze using productivity and capacity. Risk agroindustry use ISO 31000  management standard. Strategies marketing use SWOT analyses. Alternative strategies formulated by SWOT matrix. The shows that  performance of Kopi Bubuk Cap Gunung Betung Agroindustry in Bandar Lampung city is consider good, process risk, human resource risk, and incidental risks faced are low, the marketing strategies is increase production volume by maintaining and improving product quality, optimizing the use of business locations close to suppliers to increase production volume, utilizing high consumer demand by providing quality products to obtain high profits. Keywords:  agroindustry, ground coffee, marketing strategies, production performance, risk management.